Huup’s Game Changer:Transforming The Way SMEs Do Business - Albertus Aryoseto Putranto Jati; Anom Hery Suasapha; I Wayan Sukma Winarya Prabawa; Ni Made Eka Mahadewi; Hanugerah Kristiono Liestiandre; Luh Nyoman Tri Lilasari (Universitas Trisakti, 2024)
This research delves into the strategic elements crucial to the success of Small and Medium Enterprises (SMEs) within the digital promotion industry. Focusing on Huup Creative, a Bali-based company, the study explores how effective operational practices, strategic technology adoption, and robust financial planning have enabled the company to overcome resource limitations and thrive in the competitive digital landscape. Through qualitative research, including interviews with industry experts and the company's founder, the study identifies key factors that have contributed to Huup Creative's sustainability. The findings emphasize the importance of integrating technology and optimizing resources to enhance competitiveness and market resilience in the rapidly evolving digital economy. This research offers valuable insights for SMEs seeking sustainable growth in the dynamic business environment.